Evaluation of an integral transducer to determine the magnitude of the measurement error - Galindo-Castillo, Ronaldo; Campos-Magaña, Santos Gabriel; Cadena-Zapata, Martín; Zermeño-González, Alejandro; López-López, Juan Antonio; López-López, Gilbert Fresh (REVISTA TERRA LATINOAMERICANA, 2019)
The use of soil reaction force transducers coupled between the tractor and integral tillage implements are in their experimental phase in different parts of the world; however, these developments present measurement errors. The objective of this research was to corroborate the magnitude of error between an Integral Force Sensor (SIF) connected to the tractor three-point hitch and two individual sensors coupled to the work tools to monitor soil reaction forces at the integral implements. SIF was tested under laboratory conditions with calibrated equipment to register force measurements at different lever distances and at different weights, using a data acquisition system DaqBook 2000 (Measurement Computing) and a signal conditioner DBK43A (Iotech Inc.). Obtained results indicated that SIF is sensitive to the load position, equivalent to the tillage depth, in a 2 to 10% range of error. Field evaluations were performed with a chisel plow at different depths for validation, finding errors between 13.07 and 41.72%, where chisel arrangement of 0.30 m depth for front chisels and 0.30 m for the rear chisel, showed the smallest error. Applying the 10% calibration correction obtained in the laboratory for a chisel length of 0.70 to 0.90 m, the obtained error was 3.1%. Comparison of the methods spectral analysis and area under the curve, equivalent to the energy used to obtain the error, showed that there is no significant difference between the two methods.